Relationship of Objectively-Measured Habitual Physical Activity to Chronic Inflammation and Fatigue in Middle-Aged and Older Adults - Nicklas, Barbara J. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Habitual (non-exercise) physical activity (PA) declines with age, and aging-related increases in inflammation and fatigue may be important contributors to variability in PA. METHODS: This study examined the association of objectively-measured PA (accelerometry over 7 days) with inflammation (plasma interleukin-6 and C-reactive protein) and with self-reported fatigue (SF-36 Vitality) at baseline and 18 months after a diet-induced weight loss, exercise, or diet-induced weight loss plus exercise intervention in 167 overweight/obese, middle-aged, and older adults. RESULTS: At baseline, individuals with higher plasma interleukin-6, as well as those who reported feeling less energetic (more fatigued), took less steps per day and had lower PA energy expenditure and minutes of light and moderate–vigorous PA (p < .05 for all). At the 18-month follow-up, inflammation was lower in both weight loss groups, fatigue was reduced in all three groups with larger decreases in the combined group, and mean levels of habitual PA were not changed in any group. In longitudinal analyses with all groups combined, we found that participants reporting larger increases in vitality (eg, declines in fatigue) had greater increases in PA (p < .05 for all). Also, changes in steps/d and physical activity energy expenditure were indirectly associated with changes in interleukin-6 (β [SEM] for steps/d = −565 [253]; β [SEM] for physical activity energy expenditure = −22.4 [10.17]; p < .05). CONCLUSIONS: Levels of habitual PA are lower in middle-aged and older adults with higher levels of chronic inflammation and greater self-reported fatigue. In addition, participants who experienced greater declines in inflammation during the interventions had greater declines in fatigue and larger increases in PA.